Alien insect dispersal mediated by the global movement of commodities - Fenn-Moltu, Gyda; Ollier, Sébastien; Caton, Barney; Liebhold, Andrew M; Nahrung, Helen; Pureswaran, Deepa S; Turner, Rebecca M; Yamanaka, Takehiko; Bertelsmeier, Cleo (Ecological applications, 2023)
Globalization and economic growth are recognized as key drivers of biological invasions. Alien species have become a feature of almost every biological community worldwide, and rates of new introductions continue to rise as the movement of people and goods accelerates. Insects are among the most numerous and problematic alien organisms, and are mainly introduced unintentionally with imported cargo or arriving passengers. However, the processes occurring prior to insect introductions remain poorly understood. We used a unique dataset of 1,902,392 border interception records from inspections at air, land, and maritime ports in Australia, New Zealand, Europe, Japan, USA, and Canada to identify key commodities associated with insect movement through trade and travel. In total, 8939 species were intercepted, and commodity association data were available for 1242 species recorded between 1960 and 2019. We used rarefaction and extrapolation methods to estimate the total species richness and diversity associated with different commodity types. Plant and wood products were the main commodities associated with insect movement across cargo, passenger baggage, and international mail. Furthermore, certain species were mainly associated with specific commodities within these, and other broad categories. More closely related species tended to share similar commodity associations, but this occurred largely at the genus level rather than within orders or families. These similarities within genera can potentially inform pathway management of new alien species. Combining interception records across regions provides a unique window into the unintentional movement of insects, and provides valuable information on establishment risks associated with different commodity types and pathways.
Keywords: human-mediated dispersal; Austrálie; Insecta; commodity trade; invasion risk; Europe; společenstvo; introduction pathways; Evropa; zavlečené druhy; Animals; lidé; hmyz; Humans; insects; zvířata; Introduced Species; Biota; globalization; Australia